Etnični fraternalizem v priseljenskih deželah : referati s simpozija Razvoj in pomen fraternalističnega gibanja in fraternalističnih organizacij med priseljenci v priseljenskih državah = Ethnic fraternalism in immigrant countries : papers from the Symposium The Development and Significance of the Fraternal Movement and Fraternal Organizations among Immigrants in Immigrant Countries, Maribor, May 18 - May 21, 1994 - Simpozij Razvoj in pomen fraternalističnega gibanja in fraternalističnih organizacij med priseljenici v priseljenskih državah (1994 ; Maribor); Klemenčić, Matjaž (Maribor : Pedagoška fakulteta, 1996)
Povzetki ; Abstracts.
Sadrži: Fraternal benefit societies and the Slovene immigrants in the United States of America / Matjaž Klemenčić -- Restoring the foundation for research on American ethnic fraternal organization / Joel Wurl -- A home away from home : brothers in distress / Nives Sulčić -- From homeland brotherhoods to immigrant fraternalism / Ante Laušić -- SNPJ history : a general overview / Joe Evanish -- The problem of the second generation inside the SNPJ and the KSKJ as a crucial factor in the transformation of their attitudes and activities after the First World War / Majda Kodrič -- Luis Adamic and the SNPJ : Something of a home base for the author's American adventure in understanding / Henry A. Christian -- The American Mutual Life Association 1910-1994 / Rudolph M. Susel -- The Croatian Fraternal Union : protector and promoter of the Croatian cultural heritage / Ivan Čizmić -- The Croatian Fraternal Union, radicalism, and the American Labor Movment / Peter Rachleff -- Slovak frateranl-benefit societies in North America : an overview (1883-1993) / M. Mark Stolarik -- Ethnic fraternalism and working-class activism : the expanding role of Slovak fraternal organizations in the United States during the interwar years / June Granatir Alexander -- The historical model of a Hungarian fraternal association in the United States from the 1880s to 1990s / Juliana Puskas -- Fraternal and national : U.S. Ethnic fraternal benefit societies and World War II / William C. Beyer -- The Polish Women's Alliance in America : between feminism and patriotism : immigrants and their children in the USA, 1898-1930 / Adam Walaszek -- Feminism and social work : German-American women's groups in Chicago at the end of the 19th century / Christiane Harzig -- Movers and shakers : fraternalism and community in Utica, N.Y., 1890-1940 / William J. Galush -- Canadian Slovenes in the oldest fraternal organization "BLED" mutual benefit society / Milica Trebše-Štofa -- A question of dignity and morale : Macedonian brotherhoods and mutual benefit societies in Toronto, 1903-1940 / Lilian Petroff -- Organizations of Australian Slovens / Irena Čufar -- Discrimination and integration : Croatian-Australians dfter World War II / Vincent J. Batarelo -- Croatian fraternal organizations in New Zealand / Branimir Banovič -- Mutual aid activity among political emigrants in France and Switzerland, 1832-1914 / Halina Florkowska-Frančič -- Slovene achievers in the United States / Joseph Velikonja -- Ethnic "Electronic Communities" : new immigrant linkages in a wired world / Stanley D. Brunn and Darren Purcell -- Ustanovitev in razvoj Kranjsko slovenske katoliške jednote : prve slovenske centralizirane podporne organizacije v Združenih Državah Amerike / Matjaž Klemenčič, Igor Javernik -- Fraternalistične organizacije prekomurskih Slovencev v ZDA : prvo slovensko ameriško bratsko podporno društvo 1912-1942 / Mihael Kuzmič -- Jugoslovanska katoliška jednota (JSKJ) oziroma Ameriška bratska zveza (ABZ) od ustanovitve do leta 1948 / Matjaž Burjak -- Progresivne Slovenke Amerike (PSWA) : 1934-1956 / Nataša Cafnik, Bojana Cingerli / Organizacije vestfalskih Slovencev 1900-1933 / Aleš Žumer.
Bibliografske bilješke uz radove
Keywords: iseljeništvo - zbornik -- iseljenici - udruženja - zbornik -- iseljenici - etnički identitet - zbornik -- hrvatsko iseljeništvo - udruženja - zbornik -- slovensko iseljeništvo - udruženja - zbornik